2019
DOI: 10.1111/jnc.14659
|View full text |Cite
|
Sign up to set email alerts
|

Understanding depression: the hippocampus might hold the answer in a CREB‐regulated transcription coactivator

Abstract: The pathophysiology of major depressive disorders is not completely understood. In this issue of Journal of Neurochemistry, Ni and colleagues investigate the role of cyclic adenosine monophosphate response element‐binding protein (CREB)‐dependent signaling in the hippocampus on depressive‐like behaviors. This editorial highlights the key findings reported by Ni et al., (2018) and how they demonstrated the importance of CREB‐regulated transcription cofactor 1 in LPS‐induced neuroinflammation and depressive‐like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…[58] Moreover, LPS-induced depressive behaviors are dependent upon hippocampal CREB. [59] Consistently, we have shown that MR strongly affected the morphology of hippocampal neurons, the ERK-CREB-BDNF signaling pathway, and synaptic plasticity. The effects of MR on the CREB-BDNF signaling pathway and brain function might due to decrease the levels of inflammatory factors.…”
Section: Discussionsupporting
confidence: 66%
“…[58] Moreover, LPS-induced depressive behaviors are dependent upon hippocampal CREB. [59] Consistently, we have shown that MR strongly affected the morphology of hippocampal neurons, the ERK-CREB-BDNF signaling pathway, and synaptic plasticity. The effects of MR on the CREB-BDNF signaling pathway and brain function might due to decrease the levels of inflammatory factors.…”
Section: Discussionsupporting
confidence: 66%